Art and the City: Contemporary Art Galleries Districts in Paris from the End of the 19th Century until Today - Alain Quemin (Arts, 2022)
The space invested by contemporary art galleries is of utmost importance. Not only is it essential to have suitable premises, but they must also be in the right place: The physical address carries a lot of weight. The benefits to galleries of being concentrated in the same areas are twofold: They are close to their competitors, which means they are close to the art market, and thus, by their collective presence, can boost the market by encouraging collectors to go to the same places built up as art districts. Moreover, the district’s qualifying function comes about through the collective construction of this grouping of galleries from which it benefits. Today in Paris, it is the Marais neighborhood—a sector that started developing in the 1970s but even more in the 1980s and 1990s—that epitomizes the place to be for contemporary art galleries. The implantation of contemporary galleries in Paris clearly results from a historical process that led them from the 8th arrondissement to the Marais, stopping briefly at Saint-Germain-des-Prés (or the 6th arrondissement) mostly for small avant-garde structures. Studying the implantation—here in Paris—of contemporary art galleries over time illustrates the dynamics that gird the installation choices and also shows how alive the urban fabric is. Galleries enter the transformations of the urban fabric, and when they are numerous enough, they also participate directly in its development.